2011
DOI: 10.1080/15377938.2011.609399
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the Police: The Influence of Individual and Contextual Factors in a Racially Diverse Urban Sample

Abstract: People of color commonly hold more negative attitudes toward the police than do Whites. Research in this area, however, generally examines the views of African Americans, Whites, and, more recently, Hispanics. The present study contributes to this literature by exploring perceptions of the police across a sample of African American, Hispanic, Asian, and White respondents. Multivariate analysis is used to test several hypotheses linking perceptions of law enforcement to neighborhood disorder, victimization, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 64 publications
2
37
0
Order By: Relevance
“…One consistent finding of previous research on perceptions of police is that younger individuals are more likely than their older counterparts to hold negative views of the police (Brown & Benedict, 2002;Correia, Reisig, & Lovrich, 1996;Frank, Brandl, Cullen, & Stichman, 1996;Hurst & Frank, 2000;Reisig & Correia, 1997;Vogel, 2011;Wu, Sun, & Triplett, 2009). In fact, age has been regarded as an important demographic variable in determining perceptions of police (Brown & Benedict, 2002;Cao, Frank, & Cullen, 1996;Webb & Marshall, 1995).…”
Section: Demographic Characteristicsmentioning
confidence: 61%
See 1 more Smart Citation
“…One consistent finding of previous research on perceptions of police is that younger individuals are more likely than their older counterparts to hold negative views of the police (Brown & Benedict, 2002;Correia, Reisig, & Lovrich, 1996;Frank, Brandl, Cullen, & Stichman, 1996;Hurst & Frank, 2000;Reisig & Correia, 1997;Vogel, 2011;Wu, Sun, & Triplett, 2009). In fact, age has been regarded as an important demographic variable in determining perceptions of police (Brown & Benedict, 2002;Cao, Frank, & Cullen, 1996;Webb & Marshall, 1995).…”
Section: Demographic Characteristicsmentioning
confidence: 61%
“…Prior research has continuously demonstrated that victims of crime are more likely to have less favorable perceptions of police (Brown & Benedict, 2002;Cao et al, 1996;Carter, 1985;Geistman & Smith, 2007;Hurst & Frank, 2000;Vogel, 2011;Wu et al, 2009) and to be more fearful of crime than those who have not been victimized (Yun, Kercher, & Swindell, 2010). These issues are particularly salient considering it has been suggested Hispanics are disproportionally victimized (e.g.…”
Section: Contextual Variablesmentioning
confidence: 92%
“…As previously mentioned, at its worst, when certain segments of the public (i.e., racial minorities) view the police as illegitimate or failing to serve in their best interest, resistance and rioting have occurred. The literature covering the public's perception of the police indicates that minorities and members from the lower classes tend to be the most critical [5,7,8,11,[21][22][23][24].…”
Section: Public Perception Of Police Use Of Deadly Forcementioning
confidence: 99%
“…Although most citizens have a good outlook and support for the police, negative interactions whether direct or vicarious (i.e., media, friends, and family) can adversely shape their perception [8]. In her study regarding perceptions of the police, Vogel [7] asserts that, despite racial makeup, those who are more prone to possess a negative attitude of the police are younger, male, and economically disadvantaged. Binder and Scharf [24] support this position by contending that youths living in poor communities view police officers as a symbol to be hated and despised.…”
Section: Public Perception Of Police Use Of Deadly Forcementioning
confidence: 99%
See 1 more Smart Citation